Pengaruh Kualitas Layanan Dan Citra Merek Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Pelanggan Jasa JNE Di Yogyakarta - Putri Wulandari; Heru Tri Sutiono; Sri Kussujaniatun (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The purpose of this study is to analyze the effect of service quality and brand image on customer loyalty through customer satisfaction to customer service JNE in Yogyakarta. The method used was purposive sampling, with the sampling of the population is based on certain criteria namely JNE service customer in Yogyakarta have used JNE service at least 2 times. The sample in this study were 270 respondents. Data analysis methods include descriptive analysis and quanitative analysis using the SEM (Structural Equation Modeling),an analysis technique based on PLS (Structural Equation Modeling). The result of this study prove that (1) service quality has a positive and significant effect on customer satisfaction (2) brand image service quality has a positive and significant effect on customer satisfaction (3) service quality has a positive and significant effect on customer loyalty (4) brand image has a positive and significant effect on customer loyalty (5) customer satisfaction has a positive and significant effect on customer loyalty (6) service quality has a positive and significant effect on customer loyalty through customer satisfaction (7) brand image has a positive and significant effect on customer loyalty through customer satisfaction.